The Determinants of Government Environmental Performance : An Empirical Analysis of Chinese Townships - Wang, Hua (World Bank, Washington, DC, 2014)
This paper explores the determinants of government environmental performance at the local level. Chinese township governments, the lowest level in the hierarchical government structure, were selected for this exercise. The performance indicators used in the analyses include the efforts of enforcing government environmental regulations and of providing environmental services to polluting enterprises. The performance determinants identified include environmental performance of upper-level governments, local development status, industrial employment, income of workers in polluting enterprises, local environmental quality, and public pressure for environmental quality improvement. A survey of 85 townships and interviews of 151 township government leaders were conducted in three provinces of China. The statistical results show that: a) The environmental performance of upper-level governments in China strongly and positively influences the environmental efforts of the township governments. b) Public pressure has created incentives for the township governments to improve their efforts in both enforcing environmental regulations and providing environmental services, while the environmental quality did not show significant impacts. c) Higher employment in industries tends to have a negative influence on the regulatory enforcement, but a positive influence on environmental service provision. d) A higher enforcement effort and a lower service provision are associated with higher wages the workers received from industries. This implies that the industries offering higher wages to the workers are subject to more stringent environmental enforcement but receive less environmental services. 5) Richer townships tend to have less regulatory enforcement but better environmental services.